FEATURES OF REGULATION OF LABOR OF WORKERS WORKING BY THE SHIFT METHOD - Tustikbayev Ілияс Нұрболұлы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The shift approach to labor organization is widely used in domestic and international practice. The globalization of the economy due to the expansion of the geography of services, as well as the increased competition of corporations, objectively increases the importance of the concept of "remote workplace" and focuses on the study of issues arising from these labor relations. At present, the social interaction of employers with shift workers is fraught with difficulties due to the imperfection of the existing norms for organizing the shift method. This requires the formation of new mechanisms for the use of shift work. The article discusses the concept of "shift work" and comments on the analysis of scientists in this field. In the west of Kazakhstan, etc. The provisions of the Labor Code of the Republic of Kazakhstan, which regulate the rotational approach to organizing activities, are widely used not only in remote areas, but also in the current situation. The purpose of the article is to identify the features of this type of work and find ways to solve the main problems that arise in this area. A new mechanism of legal regulation of labor relations between employers and employees is needed. The formation of the social and living conditions of the personnel during the period of inter-shift rest, these processes contribute to the restoration of the potential of employees, it is necessary to consider ways to motivate their social adaptation. As a benefit in the field of remuneration of the employer providing part-time services, mechanisms are provided that allow the employer to save by reducing the economic costs of the employer when delivering workers through the employment of residents of the region where the enterprises are located. Due to the fact that this type of activity is very flexible, while maintaining the conceptual focus established by law, a number of proposals have been proposed to improve regulations on the main institutions of labor law for rotational work (contract, working hours and rest, wages, guarantees and compensation , labor protection, etc.).